Technology Adoption Problems as Bureaucracy Streamlining Tools in Indonesian Migrant Worker Protection - Irawati, Ida (Indonesian Association for Public Administration (IAPA), 2024)
The globalized economy has significantly impacted labor migration, with Indonesian migrant workers being a prominent example of this trend. This study explores the effectiveness of recent legislative reforms and technological advancements aimed at improving the protection and management of IMWs. Despite substantial efforts, including the enactment of Law No. 39 of 2004 and Law No. 18 of 2017, and the introduction of digital systems such as SIAPkerja, SISKO P2MI, SIMKIM, and Portal Peduli WNI challenges persist. Complaints from IMWs have continued to rise, highlighting gaps in the current protection framework and the integration of information systems. The study reveals that technology has not yet fully succeeded in streamlining the bureaucratic processes of IMW due to persistent issues such as constant changes in the information system, the continued requirement for uploading government-issued documents during the registration process for IMW, integration problems between systems, such as SIAPkerja, SISKO P2MI, SIMKIM, and Portal Peduli WNI, as well as underutilization of these technologies. This research employs a qualitative approach through document analysis, and in-depth interviews. A sustainable and consistent system is needed to avoid confusing service users. Furthermore, full integration between technology system must be prioritized to create a unified, real-time information flow.